2022
DOI: 10.1038/s41467-021-27926-w
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic targeting enables domain-general inhibitory control over action and thought by the prefrontal cortex

Abstract: Over the last two decades, inhibitory control has featured prominently in accounts of how humans and other organisms regulate their behaviour and thought. Previous work on how the brain stops actions and thoughts, however, has emphasised distinct prefrontal regions supporting these functions, suggesting domain-specific mechanisms. Here we show that stopping actions and thoughts recruits common regions in the right dorsolateral and ventrolateral prefrontal cortex to suppress diverse content, via dynamic targeti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 128 publications
(201 reference statements)
2
48
0
1
Order By: Relevance
“…To confirm that suppressing associate words engaged dACC and rDLPFC, we analyzed fMRI data comparing the activation between NT and T trials from the TNT phase. Using a priori dACC and rDLPFC ROIs taken from a meta-analysis of 16 retrieval suppression studies ( Apšvalka et al, 2022 ), we observed greater activity during retrieval suppression than during voluntary retrieval (dACC: +6, +23, +41; p (FWE) < 0.05, small volume corrected (SVC); rDLPFC: +36, +38, +32; p (FWE) < 0.01, SVC). With the opposite contrast (NT < T), we also confirmed decreased activity during retrieval suppression relative to voluntary retrieval in the hippocampus (left hippocampus: −33, −34, −10; p (FWE) < 0.001, SVC; right hippocampus: +24, −25, −13; p (FWE) < 0.05, SVC).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…To confirm that suppressing associate words engaged dACC and rDLPFC, we analyzed fMRI data comparing the activation between NT and T trials from the TNT phase. Using a priori dACC and rDLPFC ROIs taken from a meta-analysis of 16 retrieval suppression studies ( Apšvalka et al, 2022 ), we observed greater activity during retrieval suppression than during voluntary retrieval (dACC: +6, +23, +41; p (FWE) < 0.05, small volume corrected (SVC); rDLPFC: +36, +38, +32; p (FWE) < 0.01, SVC). With the opposite contrast (NT < T), we also confirmed decreased activity during retrieval suppression relative to voluntary retrieval in the hippocampus (left hippocampus: −33, −34, −10; p (FWE) < 0.001, SVC; right hippocampus: +24, −25, −13; p (FWE) < 0.05, SVC).…”
Section: Resultsmentioning
confidence: 98%
“…To test our a priori hypotheses, some analyses were restricted to the dACC, rDLPFC, and bilateral hippocampus. dACC and rDLPFC masks only included subregions that are commonly activated during action cancellation and memory inhibition, revealed by meta-analyses using fMRI data from stop-signal and TNT tasks ( Guo et al, 2018 ; Apšvalka et al, 2022 ). Each mask comprised the cluster of voxels revealed by conjunction analyses combining the contrasts No-Think > Think and Stop > Go ( Guo et al, 2018 , their Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have found that memory suppression decreases hippocampal activation (see Anderson and Hulbert, 2021 for a review). Effective connectivity analyses further reveal that reduced activation of these regions is caused in part by top-down control by MFG (Benoit and Anderson, 2012; Benoit et al, 2015; Benoit et al, 2016; Gagnepain et al, 2017; Apšvalka et al, 2022). But most research focuses on a few selected ROIs, such as the right MFG as the source of modulation (Paz-Alonso et al, 2013; Yang et al, 2021) and the hippocampus as the target of down-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon bears a striking resemblance to organic amnesias caused by damage to the hippocampus (for reviews, see Spiers et al, 2001). In fact, the amnesic shadow was predicted based on numerous reports of hippocampal deactivations (relative to the Think condition, as well as to passive baseline conditions) observed during studies of memory suppression (Anderson et al, 2004; Depue et al, 2007; Benoit and Anderson, 2012; Paz-Alonso et al, 2013; Gagnepain et al, 2014; Benoit et al, 2016; Yang et al, 2020; Apšvalka et al, 2022). Consistent with a role of hippocampal deactivations in successful memory control, hippocampal modulation is greatest (and predictive of suppression-induced forgetting) when unwanted memories intrude and need to be purged from awareness (Levy and Anderson, 2012; Gagnepain et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Because the inhibitory control mechanism involved in retrieval suppression is considered domain general (Anderson & Floresco, 2021; Anderson & Hulbert, 2021; Apšvalka et al, 2022; Depue et al, 2016; Gagnepain et al, 2014, 2017; Hu et al, 2017), EEG correlates of autobiographical memory control may be similar to those involved in suppressing simpler memories. Therefore, EEG correlates of autobiographical memory control may be reflected in early ERP negativities (Bergström et al, 2009b; Crespo-García et al, 2021; Mecklinger et al, 2009; Streb et al, 2016) and later sustained alpha/beta power reductions as in prior research (Legrand et al, 2020; Lin et al, 2021; Quaedflieg et al, 2020; Waldhauser et al, 2015).…”
mentioning
confidence: 99%